2017
DOI: 10.1016/j.physbeh.2017.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Examination of swallowing maneuver training and transfer of practiced behaviors to laryngeal vestibule kinematics in functional swallowing of healthy adults

Abstract: Swallowing maneuvers are routinely trained in dysphagia rehabilitation with the assumption that practiced behaviors transfer to functional swallowing, however transfer is rarely examined in the deglutition literature. The goal of this study was to train the volitional laryngeal vestibule closure (vLVC) maneuver, which is a swallowing maneuver that targets prolonged laryngeal vestibule closure (LVC). In two different training experiments, 69 healthy adults underwent Long-hold (hold vLVC as long as possible) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 43 publications
(54 reference statements)
0
36
0
Order By: Relevance
“…Guedes et al have also demonstrated adaption learning influencing LVCrt using a volitional laryngeal vestibule closure maneuver, which incorporated resistance to relaxation of laryngeal muscles during the pharyngeal stage of swallowing (i.e., similar to a Mendelsohn maneuver) [ 10 ]. As in the present study, the authors reported effects of LVCrt during natural swallowing in healthy participants immediately after a training period of 20 volitional swallows using the maneuver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Guedes et al have also demonstrated adaption learning influencing LVCrt using a volitional laryngeal vestibule closure maneuver, which incorporated resistance to relaxation of laryngeal muscles during the pharyngeal stage of swallowing (i.e., similar to a Mendelsohn maneuver) [ 10 ]. As in the present study, the authors reported effects of LVCrt during natural swallowing in healthy participants immediately after a training period of 20 volitional swallows using the maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…LVCd represented the temporal duration between the endpoint of the LVCrt measure and the initiation of arytenoid descent from the epiglottis, verified by reappearance of the supraglottal air space. Both LVCrt and LVCd have been previously reported in existing literature [ 10 ]. Both measurements were calculated in milliseconds (ms), and obtained from the pre-stimulation and post-stimulation swallows.…”
Section: Methodsmentioning
confidence: 99%
“…Second, the TVC is independent of other structures and thus can be a target for rehabilitative exercises to strengthen airway protection. A recent study of volitional LV closure maneuvers found that training TVC closure can induce safe and functional swallowing behavior as an adaptable component [19]. Third, velopharyngeal isthmus closure, epiglottis inversion, and TVC closure were prolonged in a reclining position with an increased tilting angle.…”
Section: Discussionmentioning
confidence: 95%
“…Given our swallowing maneuver targets impaired LVC, all patients underwent videofluoroscopy to confirm the presence of an LVC impairment. Quantitative LVC timing measures were calculated for each patient and were compared with the research literature impairment thresholds to determine if LVC timing was in or out of normal range . LVC was also rated using the MBSimP criteria for Component 11 (LVC) and Component 9 (Epiglottic Inversion).…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative LVC timing measures were calculated for each patient and were compared with the research literature impairment thresholds to determine if LVC timing was in or out of normal range. [15][16][17] LVC was also rated using the MBSimP criteria for Component 11 (LVC) and Component 9 (Epiglottic Inversion). Raters judged LVC as 1 = impaired or 0 = not impaired for each patient.…”
Section: Lvc Impairment Identificationmentioning
confidence: 99%